Stable isotopes as a predictor for organic or conventional classification of berries and vegetables. - Xia Zhu-Barker; Michael Liou; Diana Zapata; Jingyi Huang; William R Horwath (PLoS ONE)
Organic agriculture is expanding worldwide, driven by expectations of improving food quality and soil health. However, while organic certification by regulatory bodies such as the United States Department of Agriculture and the European Union confirms compliance with organic standards that prohibit synthetic chemical inputs, there is limited oversight to verify that organic practices, such as the use of authentic organic fertilizer sources, are consistently applied at the field level. This study investigated the elemental content of carbon (C) and nitrogen (N) and their stable isotopes (δ13C and δ15N) in seven different crops grown under organic or conventional practices to assess their applicability as a screening tool to verify the authenticity of organic labeled produce. Holm corrected Welch t-tests and a generalized linear mixed model (GLMM) were used to assess the potential of stable isotope or crop elemental content to differentiate organic vs. conventional production systems. Total C and N content or C/N ratio was not significantly different between production systems or among geographic origins for most crops. However, the average N stable isotope (δ15N) content differed, with conventional crops at 1.8 ±  2.2‰ and organic at 6.0 ±  3.4‰. A mixed model incorporating elemental contents and stable isotopes identified δ15N as the primary predictor in discriminating organic and conventional production systems. A δ15N threshold is suggested to differentiate conventional from organic grown raspberries (δ15N <  2.17‰) and strawberries (δ15N <  3.22‰), for an estimated false negative rate of 1%. Although further evaluation is needed, our extensive dataset (n = 791) captures key predictors of agricultural production systems and holds potential as a benchmark for future organic production verification.